Pendampingan Ibu Hamil Obesitas Dengan Asuhan Berkesinambungan (COC) - Gita, Estin; Nunik Adi Wahyuni; Wuri Widi Astuti (ABHIPRAYA: Jurnal Pengabdian Masyarakat Kesehatan dan Sains, 2024)
Abstract Continuity of Care is one of the efforts to reduce AKI and AKB in pregnancy to family planning. The purpose of this mentoring activity is to provide care for Mrs. "N" with obesity from the third period of pregnancy to family planning to minimize the complications. The mentoring activities carried out for Mrs. N began at 34 weeks of pregnancy until the family planning period, which was from April 8, 2024 to May 30, 2024. The methods used in this activity are interviews, observations, providing education according to the needs of patients using leaflet media and video tutorials. The results of the assistance provided, Mrs. N" G1P0000, the gestational age was obtained in the third trimester (34 weeks). The complaints experienced by Mrs. N during third trimester of pregnancy included lower back pain, frequent urination, and heartburn in the abdomen. The interventions provided include providing education about yoga gymnastics, teaching families to do efflurage massages, teaching mothers doing deep breathing relaxation techniques when there is a false his. The delivery care process takes place at the Ngadiluwih Health Center in a normal vagina, the baby is born spontaneously without any complications and is given breast milk on demand, the postpartum period takes place normally with complaints of suture pain can be overcome through KIE relaxation techniques to reduce pain. In the neonatal period, no problems are specified in the baby, and the contraceptive method chosen is AKDR. Comprehensive care given to Mrs." N" has been carried out according to the theoretical concept obtained and no gaps were found in the implementation of the care provided. Care that is carried out in a continuous and comprehensive manner can help